Indonesia Interest toward G20 Pandemic Fund: Global Health Diplomacy Perspective - Ahmada, Saqib Fardan (Jurnal Hubungan Internasional, 2024)
In the last three years, during the COVID-19 pandemic shocks, the discussion for economic recovery and global health development agenda prevailed. To date, the discussion has shifted from recovery to more extensive moves such as strengthen the current global health architecture. Specifically, prepare for the next pandemic and reduce potential risks. Countries around the world are interested in this topic and the Group of Twenty (G20), the premier economic forum summit, also focuses on this issue. This kind of "global crisis responder” experience drives the interesting discussion, how did the COVID-19 crisis respond by the G20? Answering this question, during Indonesia's G20 Presidency, the Pandemic Fund was formally introduced in collaboration with the Pandemic Fund secretariat, marked by a significant event during the G20 Joint Finance and Health Ministers' Meeting. The rationale behind establishing this fund arose from the challenges faced by low and middle-income nations in securing adequate funding for their healthcare systems amidst the COVID-19 pandemic. Depart from that, this significant achievement of the pandemic fund launching raises questions, why Indonesia has an agenda for Pandemic Fund during its presidency? This paper aims to answer this question with the framework of global health diplomacy.